Perbedaan Kemampuan Pemecahan Masalah dan Kemampuan Berpikir Kritis Siswa yang Diajarkan dengan Model Pembelajaran Reciprocal Teaching dan Problem Based Learning Siswa Kelas X SMK Kihajar Dewantara Kotapinang Tahun Pelajaran 2021-2022 - Tuti Harmidah Siregar; Yahfizham Yahfizham; Ella Andhany (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to determine the differences in problem-solving and critical thinking skills between students taught using the Reciprocal Teaching and Problem-Based Learning models in class X of SMK Ki Hajar Dewantara Kotapinang for the 2021-2022 academic year. This is a quantitative study using a quasi-experimental design. The population consists of all class X students at SMK Ki Hajar Dewantara Kotapinang in the 2021-2022 academic year, totaling 111 students. The sample used was class X AKUNTANSI 1 and X AKUNTANSI 2, each consisting of 20 students, chosen as experimental classes using Cluster Random Sampling. Data were collected from pre-tests and post-tests with problem-solving and critical thinking skill test items, then analyzed descriptively and followed by Two-Way ANOVA. The findings indicate: 1) There is no difference in problem-solving ability between students taught using the Reciprocal Teaching model and the Problem-Based Learning model in class X of SMK Ki Hajar Dewantara Kotapinang, with F_observed = 0.320 < F_table(α= 0.05) = 3.978; 2) There is a difference in critical thinking skills between students taught using the Reciprocal Teaching model and the Problem-Based Learning model in class X of SMK Ki Hajar Dewantara Kotapinang, with F_observed = 5.128 > F_table(α= 0.05) = 3.978; 3) There is a difference in both problem-solving and critical thinking skills between students taught using the Reciprocal Teaching model and the Problem-Based Learning model in class X of SMK Ki Hajar Dewantara Kotapinang, with F_observed = 0.026 > F_table(α= 0.05) = 3.936; 4) There is no interaction between the Reciprocal Teaching and Problem-Based Learning models in class X of SMK Ki Hajar Dewantara Kotapinang, with F_observed = 0.459 < F_table(α= 0.05) = 3.936.